Endogenous cross-talk of fungal metabolites - Sheridan, Kevin J.; Dolan, Stephen K.; Doyle, Sean (Frontiers in Microbiology, 2015)
Non-ribosomal peptide synthesis in fungi requires a ready supply of proteogenic and non-proteogenic amino acids which are subsequently incorporated into the nascent non-ribosomal peptide via a thiotemplate mechanism catalysed by non-ribosomal peptide synthetases. Substrate amino acids can be modified prior to or during incorporation into the non-ribosomal peptide, or following incorporation into an early stage amino acid-containing biosynthetic intermediate. These post-incorporation modifications involve a range of additional enzymatic activities including but not exclusively, monooxygenases, methyltransferases, epimerases, oxidoreductases and glutathione transferases which are essential to effect biosynthesis of the final non-ribosomal peptide. Likewise, polyketide biosynthesis is directly by polyketide synthase megaenzymes and cluster-encoded ancilliary decorating enzymes. Additionally, a suite of additional primary metabolites, for example: CoA, acetyl CoA, S-adenosylmethionine, glutathione, NADPH, malonyl CoA and molecular oxygen, amongst others are required for non-ribosomal peptide and polyketide synthesis. Clearly these processes must involve exquisite orchestration to facilitate the simultaneous biosynthesis of different types of non-ribosomal peptides, polyketides, and related metabolites requiring identical or similar biosynthetic precursors or co-factors. Moreover, the near identical structures of many natural products within a given family (e.g., ergot alkaloids), along with localization to similar regions within fungi (e.g., conidia) suggests that cross-talk may exist, in terms of biosynthesis and functionality. Finally, we speculate if certain biosynthetic steps involved in non-ribosomal peptide and polyketide synthesis play a role in cellular protection or environmental adaptation, and wonder if these enzymatic reactions are of equivalent importance to the actual biosynthesis of the final metabolite.